The role of extended synaptotagmin at membrane contact sites in cancer research - Pan, Yuetian; Strohmer, Dorothee; Feng, Shikai; Zhang, Guibin; Cui, Hongshang; Song, Yongbin (Frontiers in Cell and Developmental Biology, 2023)
Membrane contact sites (MCSs) are adjacent locations between the membranes of two different organelles and play important roles in various physiological processes, including cellular calcium and lipid signaling. In cancer research, MCSs have been proposed to regulate tumor metabolism and fate, contributing to tumor progression, and this function could be exploited for tumor therapy. However, there is little evidence on how MCSs are involved in cancer progression. In this review, we use extended synaptotagmins (E-Syts) as an entry point to describe how MCSs affect cancer progression and may be used as new diagnostic biomarkers. We then introduced the role of E-Syt and its related pathways in calcium and lipid signaling, aiming to explain how MCSs affect tumor proliferation, progression, metastasis, apoptosis, drug resistance, and treatment through calcium and lipid signaling. Generally, this review will facilitate the understanding of the complex contact biology of cancer cells.